Analisis Tingkat Kerusakan Pantai Ciberi Akibat Abrasi yang Terjadi di Disrik Abepura, Kota Jayapura pada Tahun 2014-2024 - Cheryl De Fretes; Tommi Tommi; Marsal Arung Lamba (Konstruksi: Publikasi Ilmu Teknik, Perencanaan Tata Ruang dan Teknik Sipil, 2025)
Coastal areas are transitional areas between land and marine ecosystems that are very vulnerable to natural disasters, one of which is abrasion. Coastal abrasion is the process of erosion of coastal areas caused by wave activity, ocean currents, and human activities such as infrastructure development and sand mining. Ciberi Beach (Tanjung Ciberi) located in Enggros Village, Abepura District, Jayapura City, is one of the coastal areas that experiences continuous abrasion. Its strategic location and direct facing the Pacific Ocean makes this area very vulnerable to coastal erosion. Based on the author's experience while conducting Field Work Practices at the Papua River Basin Center (BWS Papua), it is known that abrasion has caused damage to public facilities and significant coastline decline since 2019 (Cepos, 2024). Strong suspicions arose from the community based on the results of interviews conducted that the construction of the Youtefa Bridge contributed to the acceleration of abrasion. Previous research also showed that the rate of abrasion in the Yos Sudarso Bay area, including Ciberi Beach, reached 0.89 meters per year. Therefore, this study aims to analyze the level of damage to Ciberi Beach due to abrasion during the period 2014–2024, and to provide recommendations for handling to reduce the impact of damage in the coastal area.